A Forward-Looking Study on the In-Depth Development Planning of Information Technology into Teacher Education. (28th August 2022) - Zhang, Chunlan
Abstract : Teacher professional education development is actually another type of development that crosses over into a category of teacher training development that encompasses two other types of teacher training—one of which is formal and the other is informal teacher training. The other approach to teacher professional development is quite different from the professional development of professional education. The focus of the professional development of teachers is a dynamic process of development in which teachers take the initiative, actively, and consciously pursue the direction of professional development of teachers. Therefore, how to observe and study the direction of teachers' professional development from the perspective of teachers is an urgent problem that needs to be studied and solved. The professional development of teachers should be combined with their own social and teaching lives. In addition, information technology should be integrated into teachers' daily teaching life, so that it can be used as a tool to support teachers' professional development. Information technology has gradually become a tool and a means that teachers cannot do without in their teaching lives, so it is important to study and think about it from various aspects, such as the teaching process and teachers' growth experiences, and to continuously study teachers' professional development. Therefore, it is necessary to study how information technology can be used well by teachers and used by teachers to become a useful tool in teachers' educational and teaching work from various aspects. This paper first argues that the main goal of teachers' professional development is to gradually grow into expert teachers, while the main content of teachers' professional development is to understand practical knowledge, and the specific tool used by teachers in teaching is the application of social software support that can support teachers' professional development (Romanowski and Alkhateeb, 2022). This paper envisages that information technology can be integrated into the entire teaching environment and the teaching process of teachers, as a tool and a means to make the content of teachers' teaching more concise and clear. Through the use of information technology and other tools, teachers can gradually identify what they need to improve and add to their teaching process, lay the foundation for their future development, and pave the way to become better teachers with a clearer plan for their future development.